Temporal characteristics of chlorophyll fluorescence quenching and dissolved oxygen concentration as indicators of photosynthetic activity in Chlorella emersonii - El Khachia, N. -E; O'Mongain, E; Collins, A (Photosynthetica, 2008)
A simple chlorophyll fluorescence (CF) measuring system has been implemented to study temporal characteristics of chlorophyll fluorescence induction (CFI) in dark-adapted freshwater algal cultures of Chlorella emersonii. There were two different decay time constants describing the CF quenching: τ₀ (the faster) and τ₁ (the slower) with amplitudes A₀ and A₁, respectively. The relative amplitude of the faster quenching component decreased once the sample was subject to deprivation from dissolved oxygen (DO). The DO concentration of samples was monitored to validate the effects of deprivation from air contact for up to 7 d and to the effect of adding DCMU to the culture (herbicide for blocking electron transport of photosystem 2). CFI analysis and DO measurements showed that the relative amplitude of A₀ to (A₀ + A₁) and the DO concentration can be used as an indication of relative photosynthetic activity, thus allowing for the possibility to classify the physiological state of algal blooms into active and inactive states.